Modelling and monitoring geomagnetically induced currents in Ireland - Blake, Seán (Trinity College (Dublin, Ireland). School of Physics, 2017)
This thesis is the first detailed study of the effects of geomagnetic storms and geomagnetically induced currents (GICs) on the Irish power network. In order to better monitor geomagnetic storms in Ireland, a network of geomagnetic observatories (MagIE) was set up to complement Met Eireann’s Valentia observatory. Two permanent magnetometer installations with realtime communications were established in Birr and Armagh to improve realtime geomagnetic coverage. Each site calculates local K-indices in near-realtime. These K-indices, along with the MagIE data can be found at www.RosseObservatory.ie. Geolectric fields were also measured in Sligo and Leitrim at temporary installations. A test magnetometer installation identified Malin Head as a suitable site for a future addition to the MagIE network.
Keywords: Physics, Ph.D.; PhD Trinity College Dublin, 2017